Neoadjuvant S-1 with concurrent radiotherapy followed by surgery for borderline resectable pancreatic cancer: study protocol for an open-label, multicentre, prospective phase II trial (JASPAC05). Issue 10 (22nd October 2017) - Takahashi, Shinichiro; Ohno, Izumi; Ikeda, Masafumi; Kobayashi, Tatsushi; Akimoto, Tetsuo; Kojima, Motohiro; Konishi, Masaru; Uesaka, Katsuhiko
Abstract : Introduction: Borderline resectable pancreatic cancer (BRPC) can involve the portal vein, superior mesenteric vein, superior mesenteric artery, coeliac axis or hepatic artery, and has a high probability of positive surgical margins and poor prognosis after resection. Neoadjuvant chemoradiation is expected to provide substantial local control and prolong survival in patients with BRPC. Methods and analysis: This open-label, multicentre, prospective phase II trial will assess S-1 with concurrent radiotherapy as preoperative treatment for BRPC. Participants will receive S-1 (40 mg/m 2 twice daily) and concurrent radiotherapy (50.4 Gy in 28 fractions), with restaging and surgery after 3–8 weeks. Recruitment will be for a 36-month period with a minimum 24-month follow-up. The primary endpoint is the R0 resection rate for BRPC confirmed with central review. The secondary endpoints are overall survival, disease-free survival, response rate to neoadjuvant chemoradiation, pathological response rate, 2-year survival rate, surgical morbidity rate and acute and late toxicity rates. Objectives include quantifying the number of participants per year to evaluate whether randomised trials can be performed for this rare tumour. Ethics and dissemination: This trial has been approved by the National Cancer Center Institutional Review Board. Written informed consent will be obtained from all participants. Serious adverse events will be reported to the safety desk of the trial, the Data and Safety Monitoring Board and trial sites. Trial results will be submitted for peer-reviewed publication. Trial registration number: Pre-results, UMIN000009172.